Predicting post‐stroke pneumonia: the PANTHERIS score. (6th March 2013) - Harms, H.; Grittner, U.; Dröge, H.; Meisel, A.
<x xml:space="preserve">Abstract</x> Objectives Stroke‐associated pneumonia (SAP) is a common complication with a known negative impact on neurological outcome. We developed a score to identify patients at highest risk of SAP in order to promote prophylactic measures. Materials and Methods We conducted a cohort study on a neurological intensive care unit in patients suffering from acute ischemic MCA infarction. Association of predefined demographics, comorbidities, and clinical characteristics with SAP was investigated using logistic regression analysis. Results Between 2003 and 2010, a total of 335 patients were included in this analysis. Frequency of SAP was 31.3%. A 12‐point scoring system was developed based on the following factors: Glasgow Coma Scale (GCS) [GCS < 9 = 5, GCS 9–12 = 2, GCS > 12 = 0], age [<60 = 0, 60–80 = 1, >80 = 2], increase in systolic arterial blood pressure >200 mmHg within the first 24 h after admission [no = 0, yes = 2], and white blood cell count >11.000/μl [no = 0, yes = 3]. The score revealed excellent discrimination (AUC = 0.85) and calibration (Nagelkerke's R² = 0.46) properties. Predictive properties were reproduced in an internal validation group. Conclusions The PANTHERIS score is a simple scoring system for the prediction of SAP based on easy‐to‐assess parameters. By identifying patients at high risk, it may guide intense monitoring or prophylactic measures. This score needs to be validated within external datasets.